Deduction Theorem

Get Deduction Theorem essential facts below. View Videos or join the Deduction Theorem discussion. Add Deduction Theorem to your PopFlock.com topic list for future reference or share this resource on social media.

## Examples of deduction

## Virtual rules of inference

## Conversion from proof using the deduction meta-theorem to axiomatic proof

## Helpful theorems

## The deduction theorem in predicate logic

## Example of conversion

## Paraconsistent deduction theorem

## The resolution theorem

## See also

## Notes

## References

## External links

This article uses material from the Wikipedia page available here. It is released under the Creative Commons Attribution-Share-Alike License 3.0.

Deduction Theorem

This article needs attention from an expert in Mathematics. (August 2016) |

In mathematical logic, a **deduction theorem** is a metatheorem that justifies doing conditional proofs -- to prove an implication *A* -> *B*, assume *A* as an hypothesis and then proceed to derive *B* -- in systems that do not have an explicit inference rule for this. Deduction theorems exist for both propositional logic and first-order logic.^{[1]} The deduction theorem is an important tool in Hilbert-style deduction systems because it permits one to write more comprehensible and usually much shorter proofs than would be possible without it. In certain other formal proof systems the same conveniency is provided by an explicit inference rule; for example natural deduction calls it implication introduction.

In more detail, the propositional logic deduction theorem states that if a formula is deducible from a set of assumptions then the implication is deducible from ; in symbols, implies . In the special case where is the empty set, the deduction theorem claim can be more compactly written as: implies . The deduction theorem for predicate logic is similar, but comes with some extra constraints (that would for example be satisfied if is a closed formula). In general a deduction theorem needs to take into account all logical details of the theory under consideration, so each logical system technically needs its own deduction theorem, although the differences are usually minor.

The deduction theorem holds for all first-order theories with the usual^{[vague]}deductive systems for first-order logic^{[2]}. However, there are first-order systems in which new inference rules are added for which the deduction theorem fails.^{[3]} Most notably, the deduction theorem fails to hold in Birkhoff-von Neumann quantum logic, because the linear subspaces of a Hilbert space form a non-distributive lattice.

- "Prove" axiom 1:
*P*1. hypothesis*Q*2. hypothesis*P*3. reiteration of 1

*Q*->*P*4. deduction from 2 to 3

*P*->(*Q*->*P*) 5. deduction from 1 to 4 QED

- "Prove" axiom 2:
*P*->(*Q*->*R*) 1. hypothesis*P*->*Q*2. hypothesis*P*3. hypothesis*Q*4. modus ponens 3,2*Q*->*R*5. modus ponens 3,1*R*6. modus ponens 4,5

*P*->*R*7. deduction from 3 to 6

- (
*P*->*Q*)->(*P*->*R*) 8. deduction from 2 to 7

- (
*P*->(*Q*->*R*))->((*P*->*Q*)->(*P*->*R*)) 9. deduction from 1 to 8 QED

- Using axiom 1 to show ((
*P*->(*Q*->*P*))->*R*)->*R*:- (
*P*->(*Q*->*P*))->*R*1. hypothesis *P*->(*Q*->*P*) 2. axiom 1*R*3. modus ponens 2,1

- (
- ((
*P*->(*Q*->*P*))->*R*)->*R*4. deduction from 1 to 3 QED

From the examples, you can see that we have added three virtual (or extra and temporary) rules of inference to our normal axiomatic logic. These are "hypothesis", "reiteration", and "deduction". The normal rules of inference (i.e. "modus ponens" and the various axioms) remain available.

1. **Hypothesis** is a step where one adds an additional premise to those already available. So, if your previous step *S* was deduced as:

then one adds another premise *H* and gets:

This is symbolized by moving from the n-th level of indentation to the n+1-th level and saying

*S*previous step*H*hypothesis

2. **Reiteration** is a step where one re-uses a previous step. In practice, this is only necessary when one wants to take a hypothesis which is not the most recent hypothesis and use it as the final step before a deduction step.

3. **Deduction** is a step where one removes the most recent hypothesis (still available) and prefixes it to the previous step. This is shown by unindenting one level as follows:

*H*hypothesis- ......... (other steps)
*C*(conclusion drawn from*H*)

*H*->*C*deduction

In axiomatic versions of propositional logic, one usually has among the axiom schemas (where *P*, *Q*, and *R* are replaced by any propositions):

- Axiom 1 is:
*P*->(*Q*->*P*) - Axiom 2 is: (
*P*->(*Q*->*R*))->((*P*->*Q*)->(*P*->*R*)) - Modus ponens is: from
*P*and*P*->*Q*infer*Q*

These axiom schemas are chosen to enable one to derive the deduction theorem from them easily. So it might seem that we are begging the question. However, they can be justified by checking that they are tautologies using truth tables and that modus ponens preserves truth.

From these axiom schemas one can quickly deduce the theorem schema *P*->*P* (reflexivity of implication) which is used below:

- (
*P*->((*Q*->*P*)->*P*))->((*P*->(*Q*->*P*))->(*P*->*P*)) from axiom schema 2 with*P*, (*Q*->*P*),*P* *P*->((*Q*->*P*)->*P*) from axiom schema 1 with*P*, (*Q*->*P*)- (
*P*->(*Q*->*P*))->(*P*->*P*) from modus ponens applied to step 2 and step 1 *P*->(*Q*->*P*) from axiom schema 1 with*P*,*Q**P*->*P*from modus ponens applied to step 4 and step 3

Suppose that we have that ? and *H* prove *C*, and we wish to show that ? proves *H*->*C*. For each step *S* in the deduction which is a premise in ? (a reiteration step) or an axiom, we can apply modus ponens to the axiom 1, *S*->(*H*->*S*), to get *H*->*S*. If the step is *H* itself (a hypothesis step), we apply the theorem schema to get *H*->*H*. If the step is the result of applying modus ponens to *A* and *A*->*S*, we first make sure that these have been converted to *H*->*A* and *H*->(*A*->*S*) and then we take the axiom 2, (*H*->(*A*->*S*))->((*H*->*A*)->(*H*->*S*)), and apply modus ponens to get (*H*->*A*)->(*H*->*S*) and then again to get *H*->*S*. At the end of the proof we will have *H*->*C* as required, except that now it only depends on ?, not on *H*. So the deduction step will disappear, consolidated into the previous step which was the conclusion derived from *H*.

To minimize the complexity of the resulting proof, some preprocessing should be done before the conversion. Any steps (other than the conclusion) which do not actually depend on *H* should be moved up before the hypothesis step and unindented one level. And any other unnecessary steps (which are not used to get the conclusion or can be bypassed), such as reiterations which are not the conclusion, should be eliminated.

During the conversion, it may be useful to put all the applications of modus ponens to axiom 1 at the beginning of the deduction (right after the *H*->*H* step).

When converting a modus ponens, if *A* is outside the scope of *H*, then it will be necessary to apply axiom 1, *A*->(*H*->*A*), and modus ponens to get *H*->*A*. Similarly, if *A*->*S* is outside the scope of *H*, apply axiom 1, (*A*->*S*)->(*H*->(*A*->*S*)), and modus ponens to get *H*->(*A*->*S*). It should not be necessary to do both of these, unless the modus ponens step is the conclusion, because if both are outside the scope, then the modus ponens should have been moved up before *H* and thus be outside the scope also.

Under the Curry-Howard correspondence, the above conversion process for the deduction meta-theorem is analogous to the conversion process from lambda calculus terms to terms of combinatory logic, where axiom 1 corresponds to the K combinator, and axiom 2 corresponds to the S combinator. Note that the I combinator corresponds to the theorem schema *P*->*P*.

If one intends to convert a complicated proof using the deduction theorem to a straight-line proof not using the deduction theorem, then it would probably be useful to prove these theorems once and for all at the beginning and then use them to help with the conversion:

helps convert the hypothesis steps.

helps convert modus ponens when the major premise is not dependent on the hypothesis, replaces axiom 2 while avoiding a use of axiom 1.

helps convert modus ponens when the minor premise is not dependent on the hypothesis, replaces axiom 2 while avoiding a use of axiom 1.

These two theorems jointly can be used in lieu of axiom 2, although the converted proof would be more complicated:

Peirce's law is not a consequence of the deduction theorem, but it can be used with the deduction theorem to prove things which one might not otherwise be able to prove.

It can also be used to get the second of the two theorems which can used in lieu of axiom 2.

The deduction theorem is also valid in first-order logic in the following form:

Here, the symbol means "is a syntactical consequence of." We indicate below how the proof of this deduction theorem differs from that of the deduction theorem in propositional calculus.

In the most common versions of the notion of formal proof, there are, in addition to the axiom schemes
of propositional calculus (or the understanding that all tautologies of propositional calculus are to
be taken as axiom schemes in their own right), quantifier axioms, and in addition to modus ponens, one additional rule of inference, known as the rule of *generalization*: "From *K*, infer ∀*vK*."

In order to convert a proof of *G* from *T*?{*F*} to one of *F*->*G* from *T*, one deals
with steps of the proof of *G* which are axioms or result from application of modus ponens in the
same way as for proofs in propositional logic. Steps which result from application of the rule of
generalization are dealt with via the following quantifier axiom (valid whenever the variable
*v* is not free in formula *H*):

- (?
*v*(*H*->*K*))->(*H*->?*vK*).

Since in our case *F* is assumed to be closed, we can take *H* to be *F*. This axiom allows
one to deduce *F*->?*vK* from *F*->*K* and generalization, which is just what is needed whenever
the rule of generalization is applied to some *K* in the proof of *G*.

To illustrate how one can convert a natural deduction to the axiomatic form of proof, we apply it to the tautology *Q*->((*Q*->*R*)->*R*). In practice, it is usually enough to know that we could do this. We normally use the natural-deductive form in place of the much longer axiomatic proof.

First, we write a proof using a natural-deduction like method:

*Q*1. hypothesis*Q*->*R*2. hypothesis*R*3. modus ponens 1,2

- (
*Q*->*R*)->*R*4. deduction from 2 to 3

*Q*->((*Q*->*R*)->*R*) 5. deduction from 1 to 4 QED

Second, we convert the inner deduction to an axiomatic proof:

- (
*Q*->*R*)->(*Q*->*R*) 1. theorem schema (*A*->*A*) - ((
*Q*->*R*)->(*Q*->*R*))->(((*Q*->*R*)->*Q*)->((*Q*->*R*)->*R*)) 2. axiom 2 - ((
*Q*->*R*)->*Q*)->((*Q*->*R*)->*R*) 3. modus ponens 1,2 *Q*->((*Q*->*R*)->*Q*) 4. axiom 1*Q*5. hypothesis- (
*Q*->*R*)->*Q*6. modus ponens 5,4 - (
*Q*->*R*)->*R*7. modus ponens 6,3

*Q*->((*Q*->*R*)->*R*) 8. deduction from 5 to 7 QED

Third, we convert the outer deduction to an axiomatic proof:

- (
*Q*->*R*)->(*Q*->*R*) 1. theorem schema (*A*->*A*) - ((
*Q*->*R*)->(*Q*->*R*))->(((*Q*->*R*)->*Q*)->((*Q*->*R*)->*R*)) 2. axiom 2 - ((
*Q*->*R*)->*Q*)->((*Q*->*R*)->*R*) 3. modus ponens 1,2 *Q*->((*Q*->*R*)->*Q*) 4. axiom 1- [((
*Q*->*R*)->*Q*)->((*Q*->*R*)->*R*)]->[*Q*->(((*Q*->*R*)->*Q*)->((*Q*->*R*)->*R*))] 5. axiom 1 *Q*->(((*Q*->*R*)->*Q*)->((*Q*->*R*)->*R*)) 6. modus ponens 3,5- [
*Q*->(((*Q*->*R*)->*Q*)->((*Q*->*R*)->*R*))]->([*Q*->((*Q*->*R*)->*Q*)]->[*Q*->((*Q*->*R*)->*R*))]) 7. axiom 2 - [
*Q*->((*Q*->*R*)->*Q*)]->[*Q*->((*Q*->*R*)->*R*))] 8. modus ponens 6,7 *Q*->((*Q*->*R*)->*R*)) 9. modus ponens 4,8 QED

These three steps can be stated succinctly using the Curry-Howard correspondence:

- first, in lambda calculus, the function f = ?a. ?b. b a has type
*q*-> (*q*->*r*) ->*r* - second, by lambda elimination on b, f = ?a. s i (k a)
- third, by lambda elimination on a, f = s (k (s i)) k

The deduction theorem described above holds in some versions of paraconsistent logic. Usually the classical deduction theorem does not hold in paraconsistent logic. However, the following "two-way deduction theorem" does hold in one form of paraconsistent logic:^{[4]}

- if and only if ( and )

that requires the contrapositive inference to hold in addition to the requirement of the classical deduction theorem.

The **resolution theorem** is the converse of the deduction theorem. It follows immediately from modus ponens which is the elimination rule for implication.

**^**Kleene 1967, p. 39, 112; Shoenfield 1967, p. 33**^**An explicit verification of this result may be found in https://github.com/georgydunaev/VerifiedMathFoundations/blob/master/SHEN.v**^**Kohlenbach 2008, p. 148**^**Hewitt 2008

- Carl Hewitt (2008), "ORGs for Scalable, Robust, Privacy-Friendly Client Cloud Computing",
*IEEE Internet Computing*,**12**(5): 96-99, doi:10.1109/MIC.2008.107. September/October 2008 - Kohlenbach, Ulrich (2008),
*Applied proof theory: proof interpretations and their use in mathematics*, Springer Monographs in Mathematics, Berlin, New York: Springer-Verlag, ISBN 978-3-540-77532-4, MR 2445721 - Kleene, Stephen Cole (2002) [1967],
*Mathematical logic*, New York: Dover Publications, ISBN 978-0-486-42533-7, MR 1950307 - Rautenberg, Wolfgang (2010),
*A Concise Introduction to Mathematical Logic*(3rd ed.), New York: Springer Science+Business Media, doi:10.1007/978-1-4419-1221-3, ISBN 978-1-4419-1220-6. - Shoenfield, Joseph R. (2001) [1967],
*Mathematical Logic*(2nd ed.), A K Peters, ISBN 978-1-56881-135-2

*Introduction to Mathematical Logic*by Vilnis Detlovs and Karlis Podnieks Podnieks is a comprehensive tutorial. See Section 1.5.- "Deduction Theorem"

This article uses material from the Wikipedia page available here. It is released under the Creative Commons Attribution-Share-Alike License 3.0.

Popular Products

Music Scenes

Popular Artists